30-Second Biology: The 50 most thought-provoking theories of life, each explained in half a minute - Nick Battey [ Editor ] (30-second., 2016)
30-Second Biology tackles the vital science of life, dissecting the 50 most thought-provoking theories of our ecosystem and ourselves. At a time when discoveries in DNA allow us to feel more connected than ever to the natural world, this is the fastest route to an understanding of the tree of life. Whether you're dipping into the gene pool, unlocking cells, or conversing on biodiversity, this is all the knowledge you need to bring life to the dinner-party debate. The 50 most important ideas and innovations in biology dissected and explained clearly without the clutter. The fastest way to learn about cells, reproduction, animals, plants, evolution and ecosystems.